A 13-Week, Randomized Double-Blind, Placebo-Controlled, Cross-Over Trial of Ziprasidone in Bipolar Spectrum Disorder. Issue 3 (June 2015) - Patkar, Ashwin A.; Pae, Chi-Un; Vöhringer, Paul A.; Mauer, Sivan; Narasimhan, Meera; Dalley, Shannon; Loebel, Antony; Masand, Prakash S.; Nassir Ghaemi, S.
Abstract : Objective: Features of bipolarity in a major depressive disorder sample were used to define a "bipolar spectrum disorder" population for treatment with a neuroleptic agent, ziprasidone. Methods: Forty-nine acutely depressed patients were randomized to ziprasidone-washout-placebo or placebo-washout-ziprasidone in this double-blind, prospective, 13-week crossover trial. All patients met the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, criteria for a major depressive episode and were positive for at least 3 predictors of bipolarity: family history of bipolar disorder, antidepressant-induced mania, highly recurrent depressive episodes (>5), atypical depression, early onset of depression (<age 20), failure to respond to antidepressants or antidepressant tolerance. The most common bipolarity inclusion criteria were antidepressant tolerance and nonresponse, and atypical depression. Approximately 52% received ziprasidone in monotherapy, 48% as adjunct to antidepressants. Results: There was a small statistically nonsignificant benefit with ziprasidone compared with placebo on Montgomery Asberg Depression Rating Scale change [−1.5 ( p = 0.48)]. Statistical carryover effects were observed. Conclusions: Ziprasidone, alone or added to antidepressants, was not more effective than placebo in this population. A false-negative finding due to the crossover design is suggested by statistical carryover effects. Alternatively, this definition of bipolar spectrum illness may have been too nonspecific to show neuroleptic benefit, unlike other definitions, like "mixed depression." Also, this study did not test potential neuroleptic efficacy without the potentially mood-destabilizing effects of antidepressants.